Orang Tua Tunggal dalam Perspektif Al-Qur’an dan Tafsir: Implikasi Peran Ganda terhadap Kesehatan Mental Ibu - Ziyan Yusriana Asri; Fitrah Sugiarto (Kartika: Jurnal Studi Keislaman, 2026)
This article examines the challenges faced by single mothers who assume dual roles as both father and mother. The absence of one parental figure in the family structure creates psychological pressures that affect maternal mental well-being and family stability. This study employs a qualitative, literature-based approach to analyze the double burden experienced by single mothers and to explore Qur’anic interpretive perspectives on this phenomenon. Findings indicate that a holistic spiritual approach through worship, trust in Allah (tawakal), and adherence to the values of tawhid fosters patience, contentment, and inner peace. Furthermore, understanding that every hardship is accompanied by ease enables single mothers to perceive life challenges as temporary trials, enhancing psychological resilience. Well-maintained mental health also positively influences parenting patterns, promoting harmonious interactions between mother and child and ensuring the fulfillment of children’s rights in education and character development. The study highlights the significance of integrating spiritual support, emotional empowerment, and self-actualization as key strategies for sustaining the well-being of single-parent families, while underscoring the role of Qur’anic interpretation as guidance for addressing psychosocial challenges.